Analisis Integrasi Nilai-Nilai Penguatan Pendidikan Karakter Pada Buku Tematik Siswa Kelas 3 Tema 4 Kewajiban dan Hakku - Rahmad Widhianto; Mohammad Aniq Khairul Basyar; Asep Ardiyanto (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2021)
Character strengthening education in curriculum 2013 integrated to all of formal education aspects in Indonesia, the one of it is student thematic book that used as learning media in the school. The purpose that to be achieved in this research is the writer want to know the value integration of character strengthening education in the student thematic book grade 3 theme 4 "Kewajiban dan hakku". The methodology of this research is qualitative research. The analysis techniques of the research are data collection, data reduction, data presentation and conclusion/verification. The result of the research is based on observation and documentation at student thematic book grade 3 theme "kewajiban dan hakku", which is observed carefully and continuously. From the result of the research, the writer can tell that the values load of character strengthening education is integrated to all of subtheme however with different development according to each subtheme focus.